Gold Mines and Mine Fields. A Summary of the LIS Conference: The Changing Structure of Income and Social Policy in Eastern Europe: A Comparative Focus - Barbara Torrey; Timothy Smeeding (Luxembourg Income Study (LIS), 1991)
This paper summarizes the presentations made at the LIS Eastern European Conference held at LIS during the summer of 1991. It contains snippets of all papers presented and complete copies of a few of them as appendices.
Keywords: 330